2015
DOI: 10.18200/jgedc.2015214253
|View full text |Cite
|
Sign up to set email alerts
|

Creative and Critical Thinking Skills in Problem-based Learning Environments

Abstract: The human brain has the cognitive areas that can be used to think high, and need maintenance of brain development. Brain cells of human beings from birth and forever keep possession, even grew as an adult, in line with the development of maturity. The frontal lobes are dealing with abstract reasoning and problem solving more mature and parietal lobes grow in size. Students are appropriately able to manage her brain to produce results in the form of thoughts or ideas. The ability of the student to manage his br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
29

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(137 citation statements)
references
References 18 publications
3
105
0
29
Order By: Relevance
“…This result could be a basic reference in designing the learning process which is able to empower the critical thinking skills of students. For example, educators can accommodate students' critical skill using the scientific process (Gultepe, 2016), such as problem-based learning (Birgili, 2015;Ulger, 2018;Zabit, 2010).…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…This result could be a basic reference in designing the learning process which is able to empower the critical thinking skills of students. For example, educators can accommodate students' critical skill using the scientific process (Gultepe, 2016), such as problem-based learning (Birgili, 2015;Ulger, 2018;Zabit, 2010).…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…This is in line with Capraro's (2013) research that project learning is able to help students solve problems and train students to think critically, analyze, and improve higher-order thinking skills. The ability to think creatively is one of the higherorder thinking abilities, namely the ability to think divergently (Birgili, 2015;Khashani, et all, 2017) which consists of four aspects, fluency; flexibility; originality; and elaboration. Istiyono, Dwandaru & Rahayu (2018) suggests that creative thinking is a thought process that produces various possible answers when responding to problems given.…”
Section: Discussionmentioning
confidence: 99%
“…He put forward the perspective that schooling should be a laboratory for solving real-life problems (authentic problems). Problem Based Learning (PBL) Model has a general purpose to improve the skills of inquiry and problem-solving skills, behavior and social skills according to the role of adults, the skills to learn independently (Ageorges, Bacila, Poutot & Blandin, 2014;Arends, 2012;Birgili, 2015;Efendioglu, 2015;Klegeris, Bahniwal & Hurren;Skinner, Braunack-Mayer & Winning, 2015;Purichia, 2015;Temel, 2014). The results of Yuzhi (2003) aims to teach chemistry analysis and analysis of playing a role in analytical chemistry through PBL.…”
Section: Problem Based Learning (Pbl) Modelmentioning
confidence: 99%
“…One of the obstacles is that PBL model is less suitable for large information coverage or basic knowledge and some lecturers do not encourage their use (Arends, 2012). According to Birgili (2015) study found that learning models could improve the critical thinking skills of learners with procedural problem-solving activities. The results suggest for follow-up research by providing more systematic activities, so learners can remember the steps during the problem to solve their critical thinking.…”
Section: Lecturer's Behaviormentioning
confidence: 99%
See 1 more Smart Citation